Conformal invariance of massless Duffin-Kemmer-Petiau theory in Riemannian spacetimes - Casana, R.; Lunardi, J. T.; Pimentel, B. M.; Teixeira, R. G. (Iop Publishing Ltd, 2005)
We investigate the conformal invariance of massless Duffin-Kemmer-Petiau theory coupled to Riemannian spacetimes. We show that, as usual, in the minimal coupling procedure only the spin I sector of the theory - which corresponds to the electromagnetic field - is conformally invariant. We also show that the conformal invariance of the spin 0 sector can be naturally achieved by introducing a compensating term in the Lagrangian. Such a procedure - besides not modifying the spin I sector - leads to the well-known conformal coupling between the scalar curvature and the massless Klein-Gordon-Fock field. Going beyond the Riemannian spacetimes, we briefly discuss the effects of a nonvanishing torsion in the scalar case.